2010
DOI: 10.3357/asem.2303.2010
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neurological Decompression Sickness in a U-2 Pilot

Abstract: Severe neurological decompression sickness (DCS) has been a rare entity in the U.S. Air Force, including the U-2 community. In over 50 yr of operation, few U-2 pilots reported severe neurological DCS in flight despite the extreme altitudes at which they operate. This article describes a near-fatal case of neurological DCS that occurred during a combat mission. The injury left the pilot with permanent cognitive deficits that correlated with focal lesions present on magnetic resonance imaging of his brain. To ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…The reasons are unclear. Interestingly, several neurologic cases described in this study demonstrated signifi cant lesions on brain MRI, an uncommon fi nding ( 6 ). The defi nitive cause(s) for the apparent rise in both quantity and severity of DCS cases among U-2 pilots in recent years has not yet been fully explained.…”
Section: Discussionmentioning
confidence: 81%
“…The reasons are unclear. Interestingly, several neurologic cases described in this study demonstrated signifi cant lesions on brain MRI, an uncommon fi nding ( 6 ). The defi nitive cause(s) for the apparent rise in both quantity and severity of DCS cases among U-2 pilots in recent years has not yet been fully explained.…”
Section: Discussionmentioning
confidence: 81%
“…3 At this time, the precise mechanisms of CNS damage due to hypobaria are uncertain. Previously, we hypothesized that CNS damage may be caused by microbubble occlusion of small arterioles, by platelet thrombi produced by accelerated coagulation in the presence of nitrogen microbubbles, 29,30 or by direct tissue damage from microparticles and activation of proinflammatory leukocytes.…”
mentioning
confidence: 99%
“…We hypothesized that in the absence of hypobaric exposure, there should be no significant differences in either the burden or distribution of WMH between DOCs and U2Ps. The DOC median WMH volume was 0.013 cm 3 Current cognitive assessment group comparisons. There were no significant differences between U2Ps and AFPs for any of the age-adjusted MAB-II measures after applying the Sidak adjustment (table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations